Interaction between Supply Chain Management and Management Accounting Practices for Preventing Fraud to Firm’s Performance - Tulus Suryanto (International Journal of Supply Chain Management, 2018)
Although several studies have been carried out on Management Accounting Practices (MAP) and Supply Chain Management (SCM) but separately, without looking at their synergic role in an organization. Similarly, studies have examined impact of fraud and corruption on a firms performance but none has measured the impact of Management Accounting Practices or Supply Chain Management singularly or in a combined role on Firm Performance (FPP). This study aims at understanding the interaction of Management Accounting Practices and Supply Chain Management for preventing fraud for ensuring a firm performance. Hence, this study attempts to examine the mediating role of Supply Chain Management in explaining the relationship between Management Accounting Practices and Firm Performance for the purpose of preventing fraud. Data for the study was collected through a questionnaire distributed to 60 financial institutions in Indonesia which included banks, insurance, finance and leasing companies. The respondents were mainly manager level executives. The collected data was analyzed through SEM Smart PLS Package. Pearson correlation coefficients were obtained to test the hypotheses of the study. Results revealed positive relationship between Management Accounting Practices and Supply Chain Management and a positive relationship between Management Accounting Practices and Firm Performance. The study also revealed that Supply Chain Management could be used to mediate the relationship between Management Accounting Practices and Firm Performance and this interaction could be utilized to prevent fraud. These findings support the theoretically expected positive relationship between Supply Chain Management and Firm Performance. Additionally, the results of the study also reiterate the theoretical role of Supply Chain Management to consolidate Management Accounting Practices. The findings would be useful for financial managers in banking and insurance sector to consider Supply Chain Management in determining their key performance indicators (KPIs) of the firm.